Global, regional and national burden of pancreatic cancer and its attributable risk factors from 2019 to 2021, with projection to 2044 - Li, Xiao; Zhang, Yi; Yan, Zeyi; Jiang, Wenkai; Rui, Shaozhen (Frontiers in Oncology, 2025)
BackgroundTo estimate the global burden of pancreatic cancer in 2019 and 2021 including incidence, mortality, and disability-adjusted-life-years (DALYs).MethodsData on pancreatic cancer incidence, mortality and DALYs were downloaded from the Global Health Data Exchange. The 95% uncertainty intervals (UIs) were reported for annual numbers and rates (per 100,000 populations).ResultsIn 2021, there were 508,532 (95% UI: 462,09 to 547,208) incident cases of pancreatic cancer globally, of which 273,617 (250,808 to 299,347; 53.8%) were in males. The age-standardized incidence rate was 6.0 (5.5 to 6.5) per 100,000 people in 2019 and decreased to 5.9 (5.4 to 6.4) per 100,000 people in 2021. There was a 3.9% increase in the number of deaths from pancreatic cancer from 486,869 (446,272 to 517,185) in 2019 to 505,752 (461,224 to 543,899) in 2021. There was a 3.5% increase in DALYs due to pancreatic cancer, increasing from 10.9 million (10.1 to 11.7) in 2019 to 11.3 million (10.5 to 12.2) in 2021. In 2021, the highest age-standardized death rates were observed in Greenland and Monaco, and the highest age-standardized DALY rates were observed in Greenland and Uruguay. The numbers of incident cases and deaths peaked at the ages of 70 to 74 years. The pancreatic cancer burden increased as the socio-demographic index increased. To 2044, the number of incident cases and deaths will be more than 875 thousand and 879 thousand, respectively.ConclusionThe disease burden of pancreatic cancer remains high, especially in high-income regions. More cancer prevention measures are needed in the future to reduce the burden of pancreatic cancer.